Broadening our Understanding of Family Meals. Issue 1 (January 2017) - Morin, Karen H.
Abstract : Although nurses are educated to perform a nutritional assessment, they may not gather additional information about the nature of family meals. These data may highlight underlying unhealthy nutritional behaviors that could be addressed by asking a few questions that are broader in scope.